2017
DOI: 10.1021/acs.jnatprod.6b00963
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Mechanism of Action of the Marine-Derived Fungal Metabolite Trichodermamide B and Synthetic Analogues

Abstract: The trichodermamides are modified dipeptides isolated from a wide variety of fungi, including Trichoderma virens. Previous studies reported that trichodermamide B (2) initiated cytotoxicity in HCT-116 colorectal cancer cells, while trichodermamide A (1) was devoid of activity. We recently developed an efficient total synthesis for the trichodermamides A–C (1–3). Multiple intermediates and analogues were produced, and they were evaluated for biological effects to identify additional structure activity relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Library L3 comprises analogues with the truncated pyrrolidine ring, while library L4 contains structural analogues with the pyrrolidine ring bioisosterically replaced by the partially saturated 1,2-oxazine. Furthermore, 1,2-oxazine systems are encountered in several classes of biologically active natural products, most notably in the trichodermamide series [ 28 , 29 ]. These structurally novel derivatives of HPI natural products can be readily accessed by an inverse electron demand hetero-Diels-Alder reaction of indoles and transient nitrosoalkenes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Library L3 comprises analogues with the truncated pyrrolidine ring, while library L4 contains structural analogues with the pyrrolidine ring bioisosterically replaced by the partially saturated 1,2-oxazine. Furthermore, 1,2-oxazine systems are encountered in several classes of biologically active natural products, most notably in the trichodermamide series [ 28 , 29 ]. These structurally novel derivatives of HPI natural products can be readily accessed by an inverse electron demand hetero-Diels-Alder reaction of indoles and transient nitrosoalkenes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chemical shi of C-7 (d C 67.0) also indicated that the hydroxyl group was located at C-7. Thus the planar structure of compound 1 was established and the D 5,6 and 7-OH distinguished 1 from other known trichodermamides such as compounds 4-6 (D 6,7 and 5-OH). The relative conguration of 1 was deduced as 4S*, 7R*, 8R*, 9S* on the basis of the NOESY data and coupling constants.…”
Section: Resultsmentioning
confidence: 98%
“…5 Driven by the structural novelty and potent bioactivity, total synthesis of trichodermamides A-C have been achieved. [6][7][8] In our previous research, a serious of cytotoxic gliovirins (penicisulfuranols A-F) have been isolated from an active endophytic fungus Penicillium janthinellum HDN13-309.…”
Section: Respectivelymentioning
confidence: 99%
“…In the present study trichodermamide B ( 188 ; Figure 6 ) showed an IC 50 value of 3.1 μM in HeLa cell line. Compound (189) caused S-phase accumulation and cell death in HeLa cells, suggesting response to DNA double strand breaks (Jans et al, 2017 ). Chromosulfine ( 189 ; Figure 6 ), a novel cyclopentachromone sulfide, was isolated from a neomycin-resistant mutant of the marine-derived fungus, Penicillium purpurogenum G59.…”
Section: Compounds From Other Marine Derived Fungusmentioning
confidence: 99%